Community Perspectives on the Contributions of Village Officials, Health Cadres, and Mothers in Stunting Prevention: A Qualitative Study in Ngijo Village, Indonesia - An Nisa Fithri; Dian Hanifah; Arti Wardani; Eka Yuni Indah Nurmala; Ulfa Nurhidayati; Lilik Winarsih (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Stunting among children under five years old remains a critical public health issue in Indonesia, with long-term consequences for cognitive development, physical growth, and future productivity. Addressing this challenge requires strong community engagement, particularly in rural areas with limited access to health services. This study employed a qualitative design, using semi-structured interviews with village officials, nutrition officers, posyandu cadres, and mothers of children under five in Ngijo Village, Indonesia. Data were analyzed using thematic analysis following Braun and Clarke’s framework to explore stakeholder roles, implementation challenges, and expectations regarding stunting prevention and potential digital nutrition tools in Ngijo Village. Methods: A qualitative design was employed through semi-structured interviews with village officials, nutrition officers, posyandu cadres, and mothers of children under the age of five. Results: Thematic analysis was conducted to identify strategies, challenges, and expectations for digital nutrition applications. Findings revealed that prevention efforts included nutrition education, routine anthropometric monitoring, and supplementary feeding using local resources. Challenges involved limited digital literacy, resistance to counseling, and irregular posyandu cadre. Conclusion: Mothers often accessed nutrition information via YouTube and TikTok, highlighting opportunities for user-friendly digital tools. Strengthening cadre training and integrating digital applications may enhance the sustainability and replication of stunting prevention in rural contexts.